Poverty in Latin America: Perspectives and Global Framework of Policies - De la Piedra, Enrique (1985)
Profitting from renewed interest in academia and international circles on the subject of poverty, this article pretends both to call the attention on the probable evolution of poverty in Latin America as well as to outline the principal conclusions relevant to antipoverty policy design developed in the Interinstitucional Profect on Critical Poverty in Latin America, of ECLAC. The author's basic aim is to contribute towards the realization that the present seriousness of the problem of poverty is not, as has often been held, a measure of the failure of years of dedication to its analysis, but rather an indicator of the inescapable need to continue devoting resources and efforts to its study and combat.​